Energy losses of fast light ions and plasmon excitation in metal films - Kononenko, S.I.; Kalantaryan, O.V.; Zhurenko, V.P. (Вопросы атомной науки и техники, 2005)
In this paper, we present the results of measurements of the secondary emission electrons (SEE) coefficients and electron energy distributions in the forward and backward directions. The measurements were carried out in experiments with three different substances. Generalizing the results obtained makes it possible to determine the mechanisms for energy losses of a fast ion propagating in solid-state plasma. The present investigation is dedicated to thick silver foil ionoluminescence study under different incident angles and proton energies also. Possible mechanisms of light generation are discussed based on obtained experimental data.